The importance of the biochemical pharmacist in the diagnosis of idiopathic thrombocytopenic purpura (ITP) (Research, Society and Development, 2021)
Idiopathic thrombocytopenic purpura (ITP) is a disease caused by a low number of platelets that manifests itself with spots on the skin that we call purpura when it presents in a larger form and petechiae in its smaller form, the biochemical pharmacist is the professional best prepared to perform the laboratory diagnosis of the disease. The main purpose of this research is to report the importance of the biochemical pharmacist in the diagnosis of ITP. A qualitative descriptive literature search was conducted with journals posted between 2016 and 2021. ITP has no known cause; it is only known to be an autoimmune disease. The biochemical pharmacist has its importance well emphasized in the diagnosis of ITP, there are several diseases and factors that interfere with the results that can identify the disease, thus, is able to consult the patient prior to consultation and seek information such as previous diagnoses, use of continuous use drugs, among others, should also monitor the entire procedure, from collection to interpretation of results with the doctor to ensure treatment excellence. This study aimed to report the importance of the biochemical pharmacist in the diagnosis of idiopathic thrombocytopenic purpura. It was possible to notice that the pharmaceutical professional has a very important role regarding the attention to the results found and possible interferences.